Factors Influencing Smart Home Adoption Among Generation Y in Batam - Eryc Eryc; Deric Cahyadi; Andik Yulianto (Jurnal Media Computer Science, 2026)
This study aims to analyze the factors influencing smart home adoption and continuous usage intention among Generation Y in Batam City using the Extended Technology Acceptance Model (Extended TAM). The examined variables include Perceived Ease of Use, Perceived Usefulness, Cost Value, and Privacy Risk, with Satisfaction as a mediating variable and Continuous Usage as the dependent variable. A quantitative research approach was employed using a survey method, collecting data from 260 Generation Y smart home users in Batam. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that all proposed variables have a significant effect on Satisfaction and Continuous Usage. Perceived Ease of Use, Perceived Usefulness, and Cost Value play a crucial role in enhancing user satisfaction and encouraging sustained smart home usage. Interestingly, Privacy Risk shows a positive effect, suggesting that Generation Y demonstrates a high tolerance for risk as long as the perceived benefits and system protection are considered adequate. These findings confirm the applicability of Extended TAM in emerging market contexts and provide practical implications for smart home developers and technology providers.